رثاء الأب عند أحمد شوقي قصيدة (يرثي أباه) أنموذجا دراسة تحليلية - عبدالله, ليلى عثمان (Sulaimani Journal for Humanities, 2022)
This study deals with the eulogy in Ahmad Shawqi’s poems to explore the nature of this experience at the consciousness and intellectual levels on the one hand, and discovering the most important linguistic and stylistic resources on which the poet relied while expressing his special experience and then communicating it effectively, on the other. The study includes an introduction covering the problem of the study, its significance, reasons for choosing the topic, the methodology and the structure of the study. Then the researcher proceeds to highlight 1. Shawqi’s intellectual life, 2. Defining eulogy both linguistically and terminologically, and 3. The types of eulogy. The body of the research however, presents an analysis of his poem concentrating on the following: the themes of his poem, occasion of the poem and the structure of the poem which falls into two parts: the first falls into three sections, namely, the preliminary, belief in death and Almighty God’s will, and the poet’s talk about the resurrection of his father. The second part includes these sections: the interaction between the son (poet) and the father, sadness and questioning, the properties of Shawqi’s poem in eulogy of his father in terms of poetic language, true emotions and artistic imagery.